A remarkable new species of Sinotilla Lelej (Hymenoptera: Mutillidae: Smicromyrmini) from Taiwan and an overview of color diversity in East Asian mutillid females - Okayasu, Juriya; Williams, Kevin A.; Lelej, Arkady S. (Zootaxa, 2018)
A remarkable new species, Sinotilla nigrothoracica sp. nov., is described and illustrated based on females from Taiwan. This new species is characteristic in having indistinct hypostomal teeth and a black mesosoma with the lateral margins strongly convergent posteriorly. An overview of female color patterns in the far-eastern Palaearctic and eastern Oriental regions is also presented.